CASE REPORT : APPLICATION OF THEORY OF MYRA E LEVINE CONSERVATION MODEL FOR BABY E WITH LBW AND PREMATURES TREATED BY ISOLATION OF COVID RS C - Fauziah Rudhiati; Yunita Ida Rianti Sipahutar; Andria Pragholapati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Nursing care for LBW / Premature babies requires critical and specific action from nurses because the problem in LBW / Premature babies is very complex and there are still many immature organs. During the Covid 19 pandemic, where contact between parents and caregivers was limited by isolation conditions, the management of babies with premature / LBW with the confirmation of Covid 19 had to adapt to new habits with the principles of caring for LBW babies in general. The use of Myra Levine's conservation theory in providing nursing care for LBW babies in the Covid room helps nurses in touching babies as little as possible to increase their energy abilities. Myra Levine's energy conservation theory becomes a nurse's guide so that LBW babies can be handled properly in the covid isolation room without having to experience developmental problems. Recommendations based on this case report that each special unit for infant intensive care, especially the covid isolation room, make SOPs regarding the installation of PICC in LBW infants and the use of PICC in LBW / Premature babies.